Landslide Vulnerability Mapping Using Spatial Analysis Methods, Case Study in Watulimo Sub-District, Trenggalek District, East Java - Setianingsih, Asma Irma; Setiacahyandari, Husnul Khotimah; Savitri, Hanny Dyah; Nugratama, Sony (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
This study aims to determine landslde vulnerability areas in Watulimo District base on landside vulnerability factor using GIS. The method used is a weighted tiered quantitative by providing an appreciation value and using weight on various parameters in the analysis. These parameters are ranfall, slope, geology, soil type and landuse. The resul shows that there are classes of landslide vulnerability, named not vulnerable, slightly vulnerable, vulnerable, and very vulnerable. Base on the map, I is known that amost al areas in Watulimo are vulnerable to landslides. The highly vulnerable areas are distributed in Slawe, Dukuh an Watulimo villages. The northern and Southern Watulimo sub-district are slightly and non vulnerable areas. Mapping the level of vulnerability of landslide is one of the solutions to assist in determining policies to reduce the risk of disaster.